Analysis of Nutritional Problems using Focused Interviews Method in Elementary School Children (Later Childhood) in Batam City - Roza Erda; Dachriyanus Hamidi; Desmawati Desmawati; Rosfita Rasyid (Indonesian Journal of Global Health Research, 2025)
Optimal nutrition significantly impacts human health, particularly for primary school-aged children. Malnutrition manifests in various health issues, such as stunting, underweight, micronutrient deficiencies, and obesity. The prevalence of malnutrition among school-aged children in Indonesia, including Batam City, is rising yearly. This study aimed to analyse factors affecting the nutritional needs of elementary school children in Batam City. The study was conducted over one month and employed a qualitative approach. Participants included 39 respondents: 13 children, 11 parents, 5 peers, 5 teachers, and 5 school health centre officers, selected purposively. Data collection used open-ended responses through in-depth interviews. Findings revealed limited knowledge among children about balanced nutrition. All informants emphasized the importance of consuming diverse foods to meet nutritional needs, with children showing a positive attitude toward trying various foods. The respondents also highlighted the importance of avoiding impulsive snacking. Moreover, the study identified a positive relationship between physical activity and cognitive focus in learning, underscoring the need for regular physical activity. Programs addressing the specific nutritional challenges faced by children in Batam could enhance awareness and encourage healthy eating habits among elementary students.